Verifying computations with state - Braun, Benjamin; Feldman, Ariel J.; Ren, Zuocheng; Setty, Srinath; Blumberg, Andrew J.; Walfish, Michael (Symposium on Operating Systems Principles (SOSP), 2013)
When a client outsources a job to a third party (e.g., the cloud), how can the client check the result, without reexecuting the computation? Recent work in proof-based verifiable computation has made significant progress on this problem by incorporating deep results from complexity theory and cryptography into built systems. However, these systems work within a stateless model: they exclude computations that interact with RAM or a disk, or for which the client does not have the full input. This paper describes Pantry, a built system that overcomes these limitations. Pantry composes proof-based verifiable computation with untrusted storage: the client expresses its computation in terms of digests that attest to state, and verifiably outsources that computation. Using Pantry, we extend verifiability to MapReduce jobs, simple database queries, and interactions with private state. Thus, Pantry takes another step toward practical proofbased verifiable computation for realistic applications.